Rhizosphere effects on soil organic carbon processes in terrestrial ecosystems: A meta-analysis - Zhao, Xuechao; Tian, Peng; Sun, Zhaolin; Liu, Shengen; Wang, Qingkui; Zeng, Zhangquan (Geoderma, 2022)
•There were positive rhizosphere effects on soil organic C-cycling in terrestrial ecosystems.•Positive rhizosphere effects on microbial biomass and enzyme activities were universal.•Rhizosphere effects on soil respiration were positively related to that on soil organic C and total N.•Rhizosphere effects on soil respiration were negatively related to that on bacterial and fungal biomass. Rhizosphere processes are one of the most important ways in which plants affect carbon (C) cycling in terrestrial ecosystems. However, how rhizosphere processes related to C cycling are regulated by microorganisms is still poorly understood. Here, using a meta-analysis based on data compiled from 110 published articles and our measured data, we quantified the magnitudes of the rhizosphere effects on soil organic C (SOC), microbial biomass C (MBC), respiration (Rs), microbial biomass and enzymes involved in C acquisition, and discovered the linkages between the rhizosphere effect on Rs and microbial characteristics. This study provided a global-scale assessment in which positive rhizosphere effects on SOC, MBC, and Rs were observed across terrestrial ecosystems worldwide. We also found that the positive rhizosphere effects on microbial biomass and enzyme activities were likely widespread phenomena in terrestrial ecosystems. The results of the structural equation model also indicated that the rhizosphere effects on SOC and total nitrogen had positive effects on the rhizosphere effect on Rs, but the rhizosphere effects on fungal and bacterial biomass showed negative effects. Our findings highlight the importance of microbial-mediated rhizosphere Rs in global SOC cycling and suggest that the consideration of the rhizosphere effects on C cycling processes in Earth system models may improve the accuracy of predicting global SOC dynamics.